2017
DOI: 10.5507/fot.2016.018
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovery of Tetraëdriella subglobosa Pascher, a member of the Eustigmatophyceae

Abstract: An algal strain from an acidic pool near the shore of Lake Mácha, Czech Republic, was identified as Tetraëdriella subglobosa Pascher by light microscopy. Phylogenetic analysis of nuclear 18S rDNA and plastid rbcL sequence data indicated that this alga is a member of the Eustigmatophyceae, rather than the Xanthophyceae as presently classified. This is the first report of T. subglobosa since Pascher's description of the species in 1930.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…They allow for highly efficient amplification of essentially a complete rbc L gene from diverse eustigmatophytes (see also Fawley et al. , , Fawley and Fawley ). For sequencing reactions, the amplification primers were used along with the newly designed sequencing primers (provided in Table S2 in the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They allow for highly efficient amplification of essentially a complete rbc L gene from diverse eustigmatophytes (see also Fawley et al. , , Fawley and Fawley ). For sequencing reactions, the amplification primers were used along with the newly designed sequencing primers (provided in Table S2 in the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Sequencing reads were assembled with SeqAssem (SequentiX, http://www.sequentix.de/software_seqassem.php), and manually edited by visual inspection of sequencing chromatograms. Sequence data from the strains from the collection of Karen and Marvin Fawley (the five “ Pseudellipsoidion sp.” strains) were obtained using the procedures and primers described in Fawley and Fawley (). Sequences were trimmed to exclude primer regions and deposited at GenBank (accession numbers provided in Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the seminal work of Hibberd (1981), knowledge of eustigmatophyte diversity has expanded with the transfer of additional species from the Xanthophyceae (Schnepf et al 1996;Přibyl et al 2012;Fawley and Fawley 2017) and the descriptions of new taxa (Lubián 1982;Karlson et al 1996;Krienitz et al 2000;Suda et al 2002;Trzcińska et al 2014;Fawley et al 2015), including four new monotypic genera (Preisig and Wilhelm 1989;Neustupa and Němcová 2001;Hegewald et al 2007;Nakayama et al 2015). Recent culture-based and environmental DNA cloning studies have shown that the diversity of the Eustigmatophyceae is much greater than previously expected (Fawley et al 2014).…”
Section: History Of Knowledgementioning
confidence: 99%
“…Aeroterrestrial algae were also much less studied by modern molecular genetic methods until recently. This is also valid for the class Eustigmatophyceae (Stramenopiles), which includes the aquatic oilproducing Nannochloropsis/Microchloropsis [26][27][28][29][30][31][32] and some other aquatic species [33][34][35][36][37]. The same class contains peculiar, but less studied aeroterrestrial species [38][39][40].…”
Section: Introductionmentioning
confidence: 99%